The Creative spirit: harmonious living with Hildegard of Bingen - Boyce-Tillman, June (Norwich: Canterbury Press, 2000)
An introduction to the life and thought of Hildegard of Bingen - theologian, mystic, poet and musician. Her ideas about healing, the arts, science and theology and the interdependence of male and female have extraordinary relevance for today.
Hildegard's Story (by Jean Moore)-- A Woman of her time-- Justice and interrelationship-- Prayer in community-- Wisdom and the Virgin Mary-- Visions-- Healing-- The Music-- A Woman for our Time-- Creativity
Keywords: Hildegard, Saint, 1098-1179; Theology, Practical